2022
DOI: 10.3389/fonc.2022.928619
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Metabolic Syndrome and Risk of Renal Cell Cancer: A Meta-Analysis

Abstract: BackgroundMetabolic syndrome (MetS) has been related to increased risks of a variety of cancers. However, the association between MetS and the risk of renal cell cancer (RCC) remains not fully determined. This meta-analysis was conducted to investigate whether MetS is independently associated with the risk of RCC in adults.MethodsRelevant observational studies were obtained by searching PubMed, Embase, Cochrane’s Library, and Web of Science databases. Study characteristics and outcome data were extracted indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The methods of the statistics are generally consistent with those used in the previous meta-analysis of cohort studies ( 30 ). We used RR and corresponding 95% CI as the general measure for association between GV at baseline and the incidence of AF during follow-up.…”
Section: Methodsmentioning
confidence: 84%
“…The methods of the statistics are generally consistent with those used in the previous meta-analysis of cohort studies ( 30 ). We used RR and corresponding 95% CI as the general measure for association between GV at baseline and the incidence of AF during follow-up.…”
Section: Methodsmentioning
confidence: 84%
“…Researches regarding the roles of metabolic disorders in the pathogenesis and progression of cancer have become a hotspot in recent decades. As a syndrome integrating multiple common metabolic disorders, MetS has been shown to be closely related to the incidence of multiple cancers (36)(37)(38)(39)(40), but not all (41). Besides, in view of the high prevalence of MetS in patients with confirmed diagnosis of cancer (42), it is also important to determine the influence of MetS on survival of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic syndrome is characterized by obesity, insulin resistance, hypertension, and hyperlipidemia (1) and is associated with the progression of diseases such as type 2 diabetes mellitus, cardiovascular disease, and nonalcoholic steatohepatitis (3,4). Recent epidemiological studies have indicated that metabolic syndrome is also closely associated with the development of malignant tumors such as liver, bladder, renal, endometrial, pancreatic, and breast cancers (5)(6)(7)(8)(9)(10)(11). Moreover, recovery from metabolic syndrome by making lifestyle adjustments is associated with a reduced risk of pancreatic cancer compared to persistent metabolic syndrome, implying that alterations in metabolic syndrome can affect pancreatic cancer risk (12).…”
Section: Introductionmentioning
confidence: 99%